Wacana Pendisiplinan Kebertubuhan Perempuan (Analisis Wacana Kritis Sara Mills dalam Dekonstruksi “Tubuhmu Bukan Milikmu” pada Akun Instagram AILA Indonesia) - Tiara Andesti (Connected: Jurnal Ilmu Komunikasi, 2021)
Women and everything inherent in them are often seen as triggers for problems so a number of actions are needed to discipline women in accordance with the standards of value that exist in society. Discussing about women embodiment not only discusses physical bodies but also includes values that internalized through social bodies. Few months ago, the establishment of women again became a matter of debate in the realm of regulation and community organization through the discussion of sexual control stipulated in the RUU P-KS. This debate about sexual control not only occurs directly through rallies, but is also mediated through content on social media. AILA Indonesia is one of the parties that rejects the treatment of control restrictions stipulated in the RUU P-KS. Through Michel Foucault's theory of power that led to bodily discipline, this study looked at the discourse of disciplining women's embodiment conducted by AILA Indonesia as a protest against the RUU P-KS that was realized in 9 uploads of their Instagram account. The research data was analyzed using Sara Mills Critical Discourse Analysis which looked at text inequality in the depiction of women by involving analysis on three levels of words, sentences, and discourses. The results showed that the discourse of disciplining women's embodiment conducted by AILA Indonesia as the subject of research materialized to 4 main issues, namely the relevance of women and morality, positioning women as objects that are assessed and controlled, discussion of body sovereignty, and the last one is the portrayal of reviktimization. Through these four issues, AILA Indonesia describes the understanding of women's embodiment in accordance with their views. In addition, in the study also found the depiction of characters and roles are not balanced and the use of persuasive words and sentences that are able to make the reader side with a certain position.